RANCANG BANGUN SISTEM MONITORING PERKEMBANGAN BERAT TERNAK BERBASIS WEB DARI TIMBANGAN TERNAK BERBASIS IOT - Raden Sumiharto; Rizqi Raffy Imam Malik (STMIK Subang, 2026)
This study aims to design and implement a web-based livestock weight monitoring system integrated with an Internet of Things (IoT) weighing device. The system adopts a web–cloud–IoT architecture with a centralized database to ensure data integrity and consistency. An ESP32-based device reads livestock identification via RFID and measures weight using a load cell sensor, then transmits data in JSON format to a server for validation before storage in a PostgreSQL (Supabase) database. The application is developed using a full-stack Next.js framework that integrates authentication, session management, data handling, and ingestion mechanisms within a single platform. Access control is implemented using Supabase Auth and Row Level Security (RLS) policies to restrict data access based on user ownership. The ingest endpoint performs API key verification, data structure validation, and device status checking prior to recording historical data. System evaluation includes functional testing, device integration testing, load testing at 40–95 requests per second (RPS), and security assessment. The results indicate stable performance up to 90 RPS without high-severity vulnerabilities. The proposed system has potential to support digital transformation in livestock data management.